Iron-mediated inter- and intramolecular reductive cross-coupling of unactivated alkyl chlorides with aryl bromides. Issue 12 (4th March 2016) - Li, Zhuang; Sun, Hong-Mei; Shen, Qi
Abstract : Efficient inter- and intramolecular reductive cross-coupling of unactivated alkyl chlorides by Fe(PPh3 )2 Cl3 . Abstract : An efficient one-pot intermolecular reductive cross-coupling of unactivated primary and secondary alkyl chlorides bearing β-hydrogens with aryl bromides is described. A combination of magnesium turnings and a catalytic amount of the commercially available iron(iii ) complex Fe(PPh3 )2 Cl3 was used, and the conditions were also successfully extended to an intramolecular reaction for the first time. Both types of cross-coupling reactions proceed under mild conditions, involving the in situ generation of aryl Grignard reagents, and show good applicability to a variety of readily available unactivated alkyl chlorides, which have previously been challenging substrates in iron-catalyzed reductive cross-coupling reactions.